Mass transport coefficients of different nanofiltratıon membranes for biologically pre-treated textile wastewaters - Kaykioglu, Gul; Coban, Ashi; Debik, Eyup; Kayacan, B. Beril; Koyuncu, Ismail (Elsevier BV, 2011)
Abstract According to the Nernst–Planck equation, the Bs (mass transfer coefficient) and Rs (overall removal rate) values for different membrane pressures are obtained from intercept in a straight line relationship between 1/R and 1/Jv. Nernst–Planck equation was determined to be compatible due to an increase in removal rate with increasing pressure. An experimental result showed that NP030 membrane was very feasible for both wastewaters.